In Vitro Evaluation of the Antibacterial and Antioxidant Activities of Extracts from Five Medicinal Plants Traditionally Used to Treat Infections in Burundi - Nzoyisubiziki, Japhet; Ngezahayo, Jeremie; Ntakarutimana, Vestine; Nachtergael, Amandine; Duez, Pierre; Tabyaoui, Mohamed (European Scientific Journal, ESJ, 2026)
Periodically, infectious diseases emerge or re-emerge, causing epidemics or pandemics that decimate populations worldwide. Although hygiene and antibiotics have effectively controlled infections, the emergence of new pathogens resistant to existing antimicrobial agents remains a global threat. In response to the growing interest in medicinal plants as potentially safe and renewable alternatives, extracts from five plants used in traditional Burundian medicine, namely Mikania natalens DC., Helichrysum congolanum Schltr. & O. Hoffm., Justicia nyassana Lindau, Urtica massaica Mildbr. and Senecio maranguensis O. Hoffm., were evaluated for antibacterial and antioxidant potential. Antibacterial activities were assessed on fifteen bacterial strains using microdilution method and TLC-bioautography, while antioxidant activity was assessed through the DPPH• radical scavenging method. Gram-positive strains, especially S. aureus, were generally more sensitive than Gram-negative bacteria. Four plants exhibited active extracts with MICs between 250 and 1000 µg/mL, except for S. maranguensis (MICs ≥ 2000 µg/mL). M. natalensis was the most active, with dichloromethane and ethyl acetate extracts showing MICs of 250 and 500 µg/mL. Notably, its otherwise inactive extracts (MICs ≥ 1000 µg/mL) significantly potentiated β-lactams (ampicillin, oxacillin, penicillin G) and aminoglycosides (gentamycin, streptomycin) against three multi-resistant S. aureus strains, reducing their MICs by 2- to 16-fold. Methanolic extracts of all five plants displayed modest antioxidant activity with IC50s ranging from < 0.08 to 0.169 quercetin equivalents. These findings highlight the potential of Burundian medicinal plants in combating antibiotic resistances, though the safety of S. maranguensis requires caution given the well-known occurrence of genotoxic and hepatotoxic pyrrolizidine alkaloids in the genus.